Anabolic Properties of High Mobility Group Box Protein-1 in Human Periodontal Ligament Cells In Vitro - Wolf, Michael; Lossdörfer, Stefan; Römer, Piero; Bastos Craveiro, Rogerio; Deschner, James; Jäger, Andreas (Mediators of Inflammation, 2014)
High mobility group box protein-1 (HMGB1) is mainly recognized as a chemoattractant for macrophages in the initial phase of host response to pathogenic stimuli. However, recent findings provide evidence for anabolic properties in terms of enhanced proliferation, migration, and support of wound healing capacity of mesenchymal cells suggesting a dual role of the cytokine in the regulation of immune response and subsequent regenerative processes. Here, we examined potential anabolic effects of HMGB1 on human periodontal ligament (PDL) cells in the regulation of periodontal remodelling, for example, during orthodontic tooth movement. Preconfluent human PDL cells (hPDL) were exposed to HMGB1 protein and the influence on proliferation, migration, osteogenic differentiation, and biomineralization was determined by MTS assay, real time PCR, immunofluorescence cytochemistry, ELISA, and von Kossa staining. HMGB1 protein increased hPDL cell proliferation, migration, osteoblastic marker gene expression, and protein production as well as mineralized nodule formation significantly. The present findings support the dual character of HMGB1 with anabolic therapeutic potential that might support the reestablishment of the structural and functional integrity of the periodontium following periodontal trauma such as orthodontic tooth movement.